Investigation of locoregional metastatic behavior in low-grade malignant tumors of the parotid gland - Kapsalas, Andreas; Thimsen, Vivian; Varga, Regina; Agaimy, Abbas; Sievert, Matti; Balk, Matthias; Rupp, Robin; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of low-grade malignant tumors of the parotid gland following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for low-grade malignant tumors of the parotid gland by complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 94 patients formed our study sample (50 females, 44 males, female to male ratio: 1.14). The mean age was 59 years (range 15–95 years). The mean number of lymph nodes in the specimen from complete parotidectomy was 3.33 (range: 0–12). The mean number of involved lymph nodes in the parotid gland was 0.05 (range: 0–1). The mean number of lymph nodes in the specimen from the ipsilateral neck dissection was 16.2 (range 4–42). The mean number of involved lymph nodes in the neck dissection specimen was 0.09 (range: 0–2). Comparison of T1-T2 vs. T3-T4 cases revealed no statistically significant difference concerning the tumorous involvement of the lymphatic network (x2 = 0.719, p = 0.396). Conclusion: Low-grade primary malignant tumors of the parotid gland are characterized by an initially low metastatic potential, which justifies conservative forms of surgical treatment.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy

Locoregional metastatic behavior in a complex mosaic of primary malignant tumors of the parotid gland - Varga, Regina; Iro, Ann Kristin; Thimsen, Vivian; Sievert, Matti; Agaimy, Abbas; Balk, Matthias; Rupp, Robin; Grundtner, Philipp; Koch, Michael; Iro, Heinrich; Mantsopoulos, Konstantinos (American Journal of Otolaryngology, 2023)
Background: The aim of the study was to investigate primary locoregional metastatic behavior in a large sample of various malignant tumors of the parotid gland with varying grades following surgical treatment consisting of complete parotidectomy and neck dissection. Methods: The records of all patients treated for primary malignant tumors of the parotid gland by means of complete parotidectomy and neck dissection between 2007 and 2022 were studied retrospectively. Results: 196 patients formed our study sample (98 females, 98 males). The mean age was 65.7 years (22–101 years). 92 cases presented with low-grade subtypes, 19 with intermediate-grade, and 85 with high-grade carcinomas. The locoregional lymphatic network had been invaded in a total of 66/196 cases (33.6 %). The intraparotid lymph nodes were positive in 54/196 cases (27.5 %) and the cervical lymph nodes in 41/196 cases (20.9 %). In 12 out of the 66 cases with a pN+ status, the neck had been invaded without involvement of the intraparotideal lymph nodes (18.2 %). Male patients tended to suffer from more aggressive carcinomas, and high-grade subtypes presented significantly more frequently as locally advanced tumors. Higher grading was significantly associated with the involvement of the parotid (p < 0.001) and cervical (p < 0.001) lymph nodes. Intermediate and low-grade cases presented similar behavior concerning tumorous invasion of the lymphatic network of the parotid gland (p = 0.522) and the neck (p = 0.467). Conclusion: The locoregional metastatic potential of parotid malignant tumors depends upon a variety of histopathologic factors, which have to be considered in the decision-making process concerning the management of locoregional lymph nodes.
CRIS-Team Scopus Importer:2023-07-21
Keywords: High-grade; Low-grade; Malignant tumor; Neck dissection; Parotid gland; Parotidectomy